Technical complaints and adverse drug reactions reported in a regional hospital in Brazil: a cross-sectional study - Oliveira, Alan Maicon de; Rodrigues, Valéria Albuquerque Vaz; Passerini, Juliana Petini; Pedreiro, Paula Bercelli Zanoveli; Minto, Beatriz Alessi (ABCS Health Sciences, 2018)
Introduction: Adverse reactions and incidents associated with drugs cause death and threaten patient safety. In Brazil, there is still a shortage of epidemiological data on these episodes and an approach still insufficient. Objective: To describe the frequency and characteristics of reports of technical complaints and adverse drug reactions (ADRs) in a regional hospital. Methods: A cross-sectional study was carried out in a Hospital School in the northwest of the São Paulo State. Through the Anvisa’s Notivisa system, it was computed the notifications characterized as ADRs and technical complaints from June 2012 to July 2014. The notifications that were not finalized, with status pending completion or with incomplete data, were excluded. The cases of ADRs were classified according to the criterion of severity, organ system affected and characterization of the suspected drug class. The characteristics of the sex and age of the patients involved were also investigated. Data were described as single frequency and proportions. Results: A total of 151 (84.8%) notifications of possible ADRs and 27 (15.2%) of technical complaints was recorded. Women (62.9%) aged 26-59 years (42.4%) were predominant among patients reported with ADRs. The majority of the reactions were skin disorders (33.1%), of moderate severity (70.2%), coming from drugs that act on the nervous system (35.8%). Regarding the technical complaints, the extravasation of liquid from the packaging material was the most described occurrence (40.7%). Conclusion: The reports associated with drugs are recurrent in the hospital setting and the characteristics reported base knowledge on the clinical profile of the adverse events presented.